2019
DOI: 10.1007/s11144-019-01630-9
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature hydrogenation and hydrodeoxygenation of oxygen-substituted aromatics over Rh/silica: part 1: phenol, anisole and 4-methoxyphenol

Abstract: The hydrogenation and competitive hydrogenation of anisole, phenol and 4-methoxyphenol was studied in the liquid phase over a Rh/silica catalyst at 323 K and 3 barg hydrogen pressure. The rate of conversion of the reactants to products gave an order of anisole ≫ phenol > 4-methoxyphenol with hydrogenation and hydrodeoxygenation products being produced. Anisole, the most reactive substrate, was rapidly converted to methoxycyclohexane, cyclohexane, cyclohexanone and cyclohexanol, while phenol was hydrogenated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
1
14
1
Order By: Relevance
“…As may be expected, an increase in temperature resulted in higher selectivity to hydrogenolysis products as shown in Figure 4. Similar behaviour was reported with anisole hydrogenation over rhodium [14].…”
Section: Hydrogen Reactionssupporting
confidence: 86%
See 2 more Smart Citations
“…As may be expected, an increase in temperature resulted in higher selectivity to hydrogenolysis products as shown in Figure 4. Similar behaviour was reported with anisole hydrogenation over rhodium [14].…”
Section: Hydrogen Reactionssupporting
confidence: 86%
“…It has been suggested that cyclohexane is formed from cyclohexanol [17], however other authors [18] have suggested direct conversion of phenol to cyclohexane. We have shown that cyclohexanol is stable under these conditions [14] and does not form cyclohexane, therefore cyclohexane is a direct product from resorcinol. As may be expected, an increase in temperature resulted in higher selectivity to hydrogenolysis products as shown in Figure 4.…”
Section: Hydrogen Reactionsmentioning
confidence: 89%
See 1 more Smart Citation
“…Under these conditions we have shown that cyclohexane, cyclohexanone and cyclohexanol are primary products. Cyclohexanone can be hydrogenated to cyclohexanol but only once more strongly bound aromatic species have been hydrogenated [11]. At the end of the reaction conversion of hydroquinone and resorcinol is ~ 26% respectively and the overall yield of HDO products is ~ 32%, when this is compared with the HDO product yield at 26% conversion for the individual DHB isomer reactions the yield for each of them was ~ 15% giving a combined yield of 30% [6].…”
Section: Discussionmentioning
confidence: 99%
“…In this study competitive hydrogenation and low temperature HDO was examined. Studies of competitive hydrogenation are still not common [7][8][9][10] and studies of competitive HDO even less so [11][12][13]. Nevertheless, it is important that competitive reactions are considered given that when lignocellulosic biomass is converted into liquid bio-oil it can contain over 300 individual compounds.…”
Section: Introductionmentioning
confidence: 99%